2005
DOI: 10.1111/j.1461-9555.2005.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic host volatiles increase efficacy of trap cropping for management of Colorado potato beetle, Leptinotarsa decemlineata (Say)

Abstract: 1 The attractiveness of pitfall traps baited with a synthetic host volatile attractant to colonizing adult Colorado potato beetle, Leptinotarsa decemlineata (Say) was evaluated in a field setting. 2 Significantly more postdiapause, colonizing adult L. decemlineata were captured in baited than unbaited pitfall traps. 3 The potential for this synthetic kairomone to enhance the efficacy of trap cropping as a management tool was evaluated by comparing conventionally managed plots with like-sized plots bordered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Previous results have suggested that diff erential production of volatile compounds may control attraction of insects to specifi c genotypes (Reddy et al, 2004;Martel et al, 2005). Piesik et al (2008) showed that wheat stems reliably produce several volatile compounds that infl uence attraction of female WSS for oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have suggested that diff erential production of volatile compounds may control attraction of insects to specifi c genotypes (Reddy et al, 2004;Martel et al, 2005). Piesik et al (2008) showed that wheat stems reliably produce several volatile compounds that infl uence attraction of female WSS for oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge may be used to improve trapping devices that have already been tested on CPBs (Martel et al, 2005;Kuhar et al, 2006), such as those baited with the aggregation pheromone of CPB (Dickens et al, 2002) or an attractive kairomone (Dickens, 2000). This knowledge may be used to improve trapping devices that have already been tested on CPBs (Martel et al, 2005;Kuhar et al, 2006), such as those baited with the aggregation pheromone of CPB (Dickens et al, 2002) or an attractive kairomone (Dickens, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…and Scapanes autralis ( Oehlschlager et al , 2002 ). The use of host plant compounds that act as semiochemicals influencing insect behaviour is a promising method of crop protection ( Agelopoulos et al , 1999;Reddy et al , 2004;Martel et al , 2005a ). Exploitation of semiochemicals for pest management can be achieved using various strategies.…”
mentioning
confidence: 99%